Gamificação no espaço escolar: o lúdico e o ensino de história no município de Três de Maio - RS - Haiske, André (2021)
This article is the result of research and action, based on the presuppositions of bibliographic research, documentary, and applied research, which had as its theme the gamification, having been held between the years 2020 and 2021 in SETREM School in the city of Três de Maio. The research objective focused on contributing to a better learning process in history teaching through didactic games developed for sixth and seventh graders of the elementary school has as secondary objectives to produce didactic games for sixth and seventh graders of the elementary school through active methodology; to present gamification as a form of active methodology; to contextualize the gamification process as a teaching tool in history; and to reflect on the possibilities of the gamification process and its possible application in schools. The research the problem that guided the investigation was: Can games potentialize the teaching of history? The principal motivation for this research was my interest since I was a graduating student in the known active methodologies in history teaching in which I came to know about gamification. The central concepts of this work were the process of playfulness and active methodologies as the principal one the gamification. Besides the discussion and systematization of these concepts we showed 1 game built before fully mastering the concepts of gamification and developed 2 games using gamification, one focused at the sixth and the other at the seventh grades of elementary school to potentialize the teaching of history, highlighting that they have not been used so far, because of the situation of the COVID-19 pandemic. As a result of the research, we can mention the importance of gamification in teaching history, reiterate the possibilities of creating games, and display two products that can be used to help in possibilities for teaching history.